Penerapan Steganografi dan Visible Watermarking Pada Gambar Digital Untuk Perlindungan Hak Cipta - Gultom, Chelsy Elisabet; Suhartana, I Ketut Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 2 (2023): JELIKU Volume 12 No 2, November 2023, 2023)
As technology develops, almost all information and data is stored in digital form. But as we know, digital storage is more vulnerable to theft where this thing is often happen to data that people shared on the internet, include digital image. From the problem above, we do the research where we build a windows-based program using steganography with least significant bit method and visible watermarking that implement encryption hidden message and visible watermarking to the digital image we want to. This program also can decode the hidden message from the digital image that contain the message. The research prove that using the combination of steganography and visible watermarking can help the owner of the digital image to claim the copyright of their digital image. This happened because they can encrypt the proof of the ownership in the image by visible dan invisible way.